The other invisible hand. The social and economic effects of theodicy in Vico and Genovesi. Issue 3 (4th May 2022) - Bruni, Luigino; Santori, Paolo
Abstract: This paper explores the implications for modern economic thought of the debate on Theodicy, i.e., the coexistence of a good, almighty God and worldly evils. In the 17th century, this problem was raised by Pierre Bayle. The analysis focuses on the 18th century Italian school of Civil economy represented by Antonio Genovesi. Our argument is that Genovesi, and Giambattista Vico before him, reacted to Bayle's Manichaean and Atheistic view on theodicy, and that Genovesi's reaction influenced his view of the market as a place of mutual assistance where the invisible hand holds a secondary and subsidiary role compared to virtues in promoting the common good.